Disseminated Neoplasia in the Soft‐Shell Clam Mya arenaria: Membrane Lipid Composition and Functional Parameters of Circulating Cells. Issue 8 (17th June 2014) - Le Grand, Fabienne; Soudant, Philippe; Siah, Ahmed; Tremblay, Réjean; Marty, Yanic; Kraffe, Edouard
Abstract: In a previous study we compared lipid composition and functional parameters of circulating cells from Cerastoderma edule affected or not by disseminated neoplasia (neoplastic cells vs hemocytes) (Le Grand et al. Chem Phys Lipids 167:9–202013 ). Neoplastic cells presented morpho‐functional modifications concomitant to striking membrane lipid alterations: the proportion of particular plasmalogen molecular species was drastically decreased. We wanted to test whether this pattern was representative of bivalve neoplastic cells. For the purpose, a similar study was conducted on another bivalve species affected by disseminated neoplasia, the soft‐shell clam ( Mya arenaria ). Although total reactive oxygen species production was unaffected, M. arenaria neoplastic cells presented some functional alterations: phagocytosis activity was reduced by 33 %. However, lipid compositions were not drastically altered. Particularly, sterol and plasmalogen levels did not differ between both cell types (about 43 % of membrane lipids and 35 % of phospholipids, respectively in hemocytes and neoplastic cells). This could be related to the fact that disseminated neoplasia was not related to hemolymph cell proliferation in M. arenaria (0.9 ± 0.2 10 6 cell mL −1, considering both healthy and neoplastic clams, n = 6). Nevertheless this study highlighted minor but specific alterations of membrane lipid composition in M. arenaria neoplastic cells. The only phospholipid subclass in which the fatty acid profile strongly differed between both cell types was serine plasmalogen (PlsSer), with neoplastic cells presenting lower specific enrichment of 20:1n‐11 in PlsSer. Such specific alteration of membrane lipid composition strengthened the assumption of an implication of key plasmalogen molecular species in this leukemia‐like disease in bivalves.